Internal rotation and scapular position differences: A comparison of collegiate and high school baseball players - Thomas, S. J.; Swanik, K. A.; Swanik, C. B.; Kelly, J. D. (Journal of Athletic Training, 2010)
Context: Conditions such as labral and rotator cuff injuries have been linked with decreases in glenohumeral internal-rotation and increases in external-rotation motion. Also, decreased glenohumeral internal rotation is strongly associated with scapular dyskinesis.